Peran customer service sebagai public relations dalam upaya meningkatkan loyalitas nasabah bank: Studi literatur - Nurfadillah, Viona Anggraini (Maliki Interdisciplinary Journal, 2024)
Customer loyalty is an important component in the world of banking. High customer loyalty can improve the bank’s image and increase public trust. The purpose of this research is to determine the role of customer service in efforts to increase customer loyalty. This type of research is a literature review or literature review of various data sources related to research. The research results show that customer service has an important role in increasing customer loyalty. This is demonstrated by providing information that customers need, helping resolve customer complaints, offering products to customers, and providing information about product features and benefits to customers.